Online learning for dummies - Manning, Susan, 1960-; Johnson, Kevin E., 1972- (--For dummies., 2021)
Get your best education online. Whether you're a college student, adult learner, or professional in continuing education, some-and sometimes all-of your learning will happen in a virtual classroom. This book is your friendly guide to the fast-growing possibilities of this world, from choosing the right course and mastering the software to polishing up your online communication and study skills. Whatever you want from your study experience-school success, professional development, or just pursuing your passion-this is your road map to online educational success! This book will teach you to find the right course for you, prep successfully for classes, manage time online, apply for study funding, transfer credits, master the software, get the right hardware, and develop online etiquette.